2022
DOI: 10.1093/labmed/lmac122
|View full text |Cite
|
Sign up to set email alerts
|

Association of CEA, NSE, CYFRA 21-1, SCC-Ag, and ProGRP with Clinicopathological Characteristics and Chemotherapeutic Outcomes of Lung Cancer

Abstract: Objective The aim of this study was to investigate the association of serum carcinoembryonic antigen (CEA), nerve-specific enolase (NSE), cytokeratin 19 fragment (CYFRA21-1), squamous cell carcinoma antigen (SCC-Ag), and pro-gastrin-releasing peptide (ProGRP) with the clinicopathological characteristics and chemotherapeutic outcomes of patients with lung cancer. Methods A total of 189 patients with lung cancer (lung cancer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, in the differential diagnosis and efficacy evaluation of malignant tumors, CEA is still important. Increased CEA in non-small cell lung cancer patients indicates that recurrence and metastasis are more likely to occur, and recent studies have shown that CEA is valuable for predicting prognosis in non-small cell lung cancer patients (15)(16)(17)(18). The TNM staging system is used to comprehensively evaluate the stage of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the differential diagnosis and efficacy evaluation of malignant tumors, CEA is still important. Increased CEA in non-small cell lung cancer patients indicates that recurrence and metastasis are more likely to occur, and recent studies have shown that CEA is valuable for predicting prognosis in non-small cell lung cancer patients (15)(16)(17)(18). The TNM staging system is used to comprehensively evaluate the stage of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of tumor markers in the blood has certain reference values for tumor screening and diagnosis. Tumor markers in the gastrointestinal tract mainly include CEA, CA19-9, CA125, and CA72-4, of which CEA has the highest sensitivity ( 23 26 ), and tumor markers in lung cancer include CEA, CYFRA21-1, SCC, and NSE ( 27 ). In our case, tumor markers were elevated in both the gastrointestinal tract and the lung, indicating that the tumor markers were nonspecific and cannot be relied on alone to determine the origin of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Their expression has been detected mainly at the tumor level and to a markedly lesser extent as circulating molecules. SCC-A is the most studied biomarker and is overexpressed in distinct squamous cell cancers, including the following: Esophagus, lung, head, neck, and in anal canal, and uterine cervix, as well as in vulvar and penile carcinoma (101)(102)(103)(104)(105). Meanwhile, YKL-40 has demonstrated high tissue levels in anal carcinoma and it has been detected in the plasma of patients with esophageal cancer (106) and CA-125 showed relatively high circulating levels in vulvar carcinoma (107).…”
Section: Expression Of Circulating Biomarkers In Other Hpvrelated Can...mentioning
confidence: 99%